"Obviously, That Worked": Examining Links between Data Use and Classroom Instruction. Issue 5 (September 2016) - Van Lare, Michelle D.
Ever-growing expectations exist for educators to use assessments to collect, analyze, and interpret data, but how, if at all, are these processes affecting instruction? This descriptive case study of one team of second grade teachers offers an analysis of the links between teachers' use of data within their collaborative team meetings and instructional decisions in the classroom Findings illustrate three activities that linked teacher discussions and instruction in classrooms: troubleshooting and normalizing expectations, targeting instruction, and identifying what worked While these links tightly coupled teachers collaborative use of data and assessments with their classroom instruction, they did so by prioritizing isolated instructional responses focused on discrete skills and specific instructional strategies. Implications include building structures that reframe what teachers mean by "worked" when inquiring into student learning.